Dynamic behavior of materials. proceedings of the 2015 Annual Conference on Experimental and Applied Mechanics /: proceedings of the 2015 Annual Conference on Experimental and Applied Mechanics. Volume 1 : ([2016]) - Unknown
No abstract available